"Not Designed for Us": How Science Museums and Science Centers Socially Exclude Low‐Income, Minority Ethnic Groups. Issue 6 (11th September 2014) - DAWSON, EMILY
ABSTRACT This paper explores how people from low‐income, minority ethnic groups perceive and experience exclusion from informal science education (ISE) institutions, such as museums and science centers. Drawing on qualitative data from four focus groups, 32 interviews, four accompanied visits to ISE institutions, and field notes, this paper presents an analysis of exclusion from science learning opportunities during visits alongside participants' attitudes, expectations, and conclusions about participation in ISE. Participants came from four community groups in central London: a Sierra Leonean group (n = 21), a Latin American group (n = 18), a Somali group (n = 6), and an Asian group (n = 13). Using a theoretical framework based on the work of Bourdieu, the analysis suggests ISE practices were grounded in expectations about visitors' scientific knowledge, language skills, and finances in ways that were problematic for participants and excluded them from science learning opportunities. It is argued that ISE practices reinforced participants preexisting sense that museums and science centers were "not for us." The paper concludes with a discussion of the findings in relation to previous research on participation in ISE and the potential for developing more inclusive informal science learning opportunities.